The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.5624/isd.2014.44.4.263
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis prediction from the mandible using cone-beam computed tomography

Abstract: PurposeThis study aimed to evaluate the use of dental cone-beam computed tomography (CBCT) in the diagnosis of osteoporosis among menopausal and postmenopausal women by using only a CBCT viewer program.Materials and MethodsThirty-eight menopausal and postmenopausal women who underwent dual-energy X-ray absorptiometry (DXA) examination for hip and lumbar vertebrae were scanned using CBCT (field of view: 13 cm×15 cm; voxel size: 0.25 mm). Slices from the body of the mandible as well as the ramus were selected an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(75 citation statements)
references
References 43 publications
4
70
0
1
Order By: Relevance
“…Indices developed by Barngkgei et al. and Koh and Kim were used . Briefly, on the axial image at the mental foramen area, the anteroposterior cursor was made tangent to the bone (Figure A).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indices developed by Barngkgei et al. and Koh and Kim were used . Briefly, on the axial image at the mental foramen area, the anteroposterior cursor was made tangent to the bone (Figure A).…”
Section: Methodsmentioning
confidence: 99%
“…The use of dental radiographs for osteoporosis screening has been extensively evaluated; however, using computed tomography techniques (multidetector computed tomography [MDCT] or cone‐beam computed tomography [CBCT]) for such a purpose has been infrequently investigated due to radiation dose concerns . In addition, these techniques are not the usual prescribed imaging techniques for dental patients, which means they would be of low value for opportunistic screening.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the femoral neck and the forearm bones are not directly associated with each other, similar research effort has been conducted on the relationship between BMDs from different sites. In [25][26][27], the results showed that that some parameters from the cortical bone in distal radius and ulnar on anteroposterior radiograph could reflect the femoral neck BMD. In [25], the distal radius BMD was correlated with the ratio of the outside cortical shell diameter to the inside cortical shell diameter at the metaphyseal/diaphyseal junction.…”
Section: Discussionmentioning
confidence: 96%
“…In [25], the distal radius BMD was correlated with the ratio of the outside cortical shell diameter to the inside cortical shell diameter at the metaphyseal/diaphyseal junction. In [26], radiologic density of dental structure from CBCT imaging could provide information of lumbar vertebra and femoral neck. In [27], the radial bicortical widths were measured at 50 and 70 mm proximal to the distal ulnar articular surface, and the mean bicortical width was compared with each patient's femoral BMD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation